La participación ciudadana: Rol del estado inserto en la Constitución de 2008 - Rodas Coloma, Alejandro (2024)
The article shows how the new post- neoliberal processes, which seeks a deeper social participation, have tried to build participation as a way to broaden the base of support and reformulation of the exercise of democracy. To that end, in sorne cases it has chosen vertical aclions, on other occasions, as in Ecuador, has built a system that catalyzes this social participation from institutional structures created for this purpose or whose functions the mentioned role. That goes for the so-called Transparency lunction and Social Control makes to result in the consolidation of what is called the social power or fifth power, whose legitimacy must be analyzed in the heat of legal beyond the political intricacies.